A call for the examination of multiracial students in Minority Serving Institutions. Issue 174 (5th November 2021) - Olivo, Victoria Barbosa; Cepeda, Rebecca
Abstract: This article describes the limited research on multiracial students at Minority Serving Institutions (MSIs). We call on scholars studying MSIs to question their conceptualizations of race and the ways they promote the assumption of monoracial identities.